2009
DOI: 10.1007/s12031-009-9262-z
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Lipids In The Nicotinic Acetylcholine Receptor Microenvironment

Abstract: The structural and functional properties of the nicotinic acetylcholine receptor (AChR), the archetype molecule in the superfamily of Cys-looped ligand-gated ion channels, are strongly dependent on the lipids in the vicinal microenvironment. The influence on receptor properties is mainly exerted by the AChR-vicinal ("shell" or "annular") lipids, which occur in the liquid-ordered phase as opposed to the more disordered and "fluid" bulk membrane lipids. Fluorescence studies from our laboratory have identified di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Likewise, lipid microenvironment in form of "shell" or "annular" lipids has a strong effect on the structural and functional properties of the nicotinic receptors [49-51] as cholesterol is an absolute requirement for their stability, supramolecular organization and function [52-54]. …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, lipid microenvironment in form of "shell" or "annular" lipids has a strong effect on the structural and functional properties of the nicotinic receptors [49-51] as cholesterol is an absolute requirement for their stability, supramolecular organization and function [52-54]. …”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations, it was demonstrated that even slight changes in adjacent lipid structure can cause important alterations in the function of LGICs by changing the energetics of conformational transitions in the protein structure (Fantini and Barrantes, 2009; Barrantes et al, 2010). Besides their interaction with membranes, menthol and other monoterpenes can bind directly to residues of the transmembrane domains and alter the functional properties of LGICs.…”
Section: Mechanisms Of Menthol Actionsmentioning
confidence: 99%
“…But the interaction of TM2 with the rest of the transmembrane domain is not trivial. Both mutations in the lipid-facing TM4 helix [26-33] and changes in lipid environment [20, 34] have been shown to affect ion channel assembly and function. The role of TM4 in stabilizing the transmembrane domain is supported by the observation that pentameric assembly of homologous receptors truncated after TM3 were rescued in oocytes by coexpressing the complementary TM4 helix, even though TM4 does not directly form a subunit interface [33].…”
Section: Introductionmentioning
confidence: 99%